The Mental Health in Diabetes Service (MINDS) to enhance psychosocial health: study protocol for a randomized controlled trial. Issue 1 (December 2016) - O'Brien, Casey; Ski, Chantal; Thompson, David; Moore, Gaye; Mancuso, Serafino; Jenkins, Alicia; Ward, Glenn; MacIsaac, Richard; Loh, Margaret; Knowles, Simon; Rossell, Susan; Castle, David
Abstract Background After a diagnosis of diabetes mellitus, people not only have to cope with the physical aspects and common complications that require daily self-management, they are also faced with ongoing psychosocial challenges. Subsequently they find themselves having to navigate the health system to engage multidisciplinary supports; the combination of these factors often resulting in reduced health-related quality of life. To maintain optimal diabetes control, interventions need to incorporate psychosocial supports and a skill base for disease management. Therefore, our aim was to evaluate an 'Optimal Health Program' that adopts a person-centred approach and engages collaborative therapy to educate and support the psychosocial health of people diagnosed with type I or II diabetes. Methods This prospective randomised controlled trial will include 166 people diagnosed with diabetes: 83 in the intervention (Optimal Health Program) and 83 in the control (usual care) group. Participants with type diabetes mellitus will be recruited through hospital outpatient clinics and diabetes community organisations. Participants in the intervention group will receive nine (8 + 1 booster session) sequential sessions, based on a structured treatment manual emphasising educational and psychosocial support self-efficacy and skills building. The primary outcome measures will be generalised self-efficacy (GSE) and health-related quality of life (AQoL-6D and EQ-5D). Secondary measures will be anxiety and depression (HADS), social and workplace functioning (WSAS), diabetes-related quality of life (DQoL), diabetes-related distress (PAID), and type of coping strategies (Brief COPE). In addition, a health economic cost analysis and process evaluations will be performed to assess the economic cost and efficacy of the program's operations, implementation and service delivery. Discussion We envisage that the Optimal Health Program's emphasis on self-efficacy and self-management will provide participants with the skills and knowledge to achieve increased empowerment and independence in aspects of health, which in turn, will help participants deal more effectively with the physical and psychosocial complexities of diabetes. Trial registration ACTRN12614001085662 . Registered on 10 October 2014.